The Effect of Repetitive Transcranial Magnetic Stimulation on Lower-Limb Motor Ability in Stroke Patients: A Systematic Review - Fan, Huiliu; Song, Yang; Cen, Xuanzhen; Yu, Peimin; Bíró, István; Gu, Yaodong (Frontiers in Human Neuroscience, 2021)
Repetitive transcranial magnetic stimulation (rTMS) is fundamental on inducing neuroplastic changes and promoting brain function restoration. Nevertheless, evidence based on the systematic assessment of the implication of rTMS in stroke patients is inadequacy. This study aimed to evaluate the value of rTMS in the treatment of lower-limb motor dysfunction in stroke patients via gait characteristics. The electronic literature search was performed in ScienceDirect, Google Scholar, and PubMed databases using ‘repetitive transcranial magnetic stimulation’, ‘gait’ and ‘stroke’ between 2000 and 2020. By screening all the identified studies, a total of 10 studies covering 257 stroke patients were included by matching the inclusion criteria, involving both rTMS with high (≧5Hz) and low frequency (<5Hz). Despite the limited study number and relatively high risk of bias, the results of this review primarily confirmed the enhancing effects of rTMS on the lower-limb motor ability (e.g. gait and balance) of stroke patients. In addition, 15- to 20-min course of rTMS for 2 to 3 weeks was found to be the most common setting, and 1Hz and 10Hz were the most common used low and high frequencies, respectively. These results might have significant clinical applications for patients with weakened lower-limb mobility after a stroke. Nevertheless, more rigorous studies in this field are much warranted.